Rekomendasi Rancangan Pengelolaan Situs Cagar Budaya Perahu Punjulharjo di Rembang, Jawa Tengah - Agni Sesaria Mochtar (Balai Arkeologi Yogyakarta, 2020)
The Punjulharjo boat is a wooden watercraft, built in the traditional Southeast Asian boat building technique called lashed-lug tradition. It was found in 2008, excavated, and later was dismantled for a lengthy conservation process. In early 2018, the hull was reassembled to be displayed for public. The site where the boat was found, and now displayed, has been listed as a heritage site under the Regulation of The Minister of Culture and Tourism No. 57 of 2010, but a management plan of it is still non-existent. Recommendations in this proposed management plan was amassed in accordance to international standards on site management plan. Data was collected from direct site observation, with the assistance of consultations to related references. This plan outlines objectives and strategy in managing the Punjulharjo site, and hopefully can serve as guidelines for the Regional Government of the District of Rembang as the manager of the site.